Answer:
5x - 6 = 8
Explanation:
1. We know that we don't know the actual number. We can use x to sub in for that number.
2. We also know that the equivalent eventually gets us to 8, so write:
3. The equation multiplies the number by 5, and then subtracts 6. It must be in this order because of PEMDAS. Write like so:
You could solve it too, if you like:
- 5x = 8+6
- 5x = 14
- x = 14/5
- x= 2.8
Then feel free to check your answer, substituting 2.8 for x:
- 5(2.8) - 6 = 8
- 14 - 6 = 8
- 8 = 8
Hope that helped